Memperbaiki Kemampuan Guru dalam Mengelola Pembelajaran IPA di Sekolah Dasarmelalui Supervisi Klinis, Supervisi Akademik dan Supervisi Kelas - Akhmad Syakrani (Universitas Sebelas Maret, 2018)
School action research aims to improve the ability of teachers in managing IPA learning in elementary school through clinical supervision, academic supervision and supervision classes. School action research conducted two cycles. The I-cycle related to the design of the device, and the RPP cycle II of the management learning. The subject is the teacher of class V IPA SDN Sungai Tiung4. The research was carried out on the even semester 2016/2017.Data design device RPP retrieved from the device's assessment of the RPP made teachers. Data management of the learning derived from the results and the process of learning. All data were analyzed in quantitative descriptive.The results showed 1) the ability of teachers in designing RPP devices can be improved, 2) the ability of teachers in managing learning seen from student learning outcomes, namely the results of group work students in solving LKS questions are good, observations of student performance are also classified as good group activities during the learning process are also good.